Mortality risk stratification for Takotsubo syndrome: Evaluating CRP measurement alongside the InterTAK prognostic score - Loïc Faucher; Kensuke Matsushita; Shinnosuke Kikuchi; Taraneh Tatarcheh; Benjamin Marchandot; Amandine Granier; Said Amissi; Antonin Trimaille; Laurence Jesel; Patrick Ohlmann; Kiyoshi Hibi; Valérie Schini‐Kerth; et al. (ESC Heart Failure)
Abstract Background and objectives Initially described as a benign acute cardiomyopathy, Takotsubo syndrome has been linked to elevated mortality rates. Emerging evidence suggests that unresolved myocardial inflammation may contribute to this adverse prognosis. This study aimed to evaluate the incremental prognostic utility of C‐reactive protein (CRP) in conjunction with the InterTAK prognosis score for stratifying long‐term mortality in Takotsubo syndrome. Methods A retrospective analysis was conducted from a multicentre registry encompassing 307 patients diagnosed with Takotsubo syndrome between 2008 and 2020. Patients were stratified into quartiles based on the InterTAK prognosis score. The discriminatory potential of CRP in predicting long‐term mortality was assessed. The primary endpoint was defined as all‐cause mortality within 1 year. Results A stepwise increase of CRP at discharge that corresponds to INTERTAK quartiles was observed: 9.5 mg/L (25th percentile) in the first quartile, 15.8 mg/L (median) in the second quartile, 25.3 mg/L (75th percentile) in the third quartile and 41.2 mg/L (maximum) in the fourth quartile. Receiver operating‐characteristic curves analysis revealed that CRP value at discharge was predictive of 1 year mortality (area under the curve = 0.81; 95% confidence interval = 0.68–0.90) with an optimal threshold set at 33 mg/L (sensitivity: 65%; specificity: 87%). When considering the InterTAK score, the incorporation of CRP at discharge with a cut‐off of 33 mg/L exhibited a significant enhancement in the prediction of 1 year mortality in ‘intermediate’ risk (25% vs. 1%; P = 0.008) or ‘very high’ risk (40% vs. 10%; P = 0.02) patients. Conclusions In Takotsubo syndrome, the persistence of inflammatory burden at hospital discharge emerged as an independent predictor of 1 year mortality, augmenting the predictive capacity of the conventional InterTAK prognosis score.